PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KREDIT BERMASALAH BANK UMUM KONVENSIONAL DAN PEMBIAYAAN BERMASALAH BANK UMUM SYARIAH - Putri, Elsa Pradika (Jurnal Ilmiah Mahasiswa FEB, 2015)
Credit or financing become important part to affect stability of banking business, so it needs a good management of  credit or  financing to  reduce credit or  finance risk as  much as  can. The occurrence of credit or financing problems can be influenced by internal and external factors. Internal factors related to the policy or management from the bank, while external factors related to macroeconomic situation in Indonesia. This research attempts to find out impact of internal factors such as LDR or FDR and CAR and external factors such as GDP, inflation, and BI rate to non performing loan of conventional bank and non performing financing of sharia bank.The data analysis method used the multiple linear regression with Error Correction Model (ECM). The results showed that LDR or FDR, CAR, GDP, inflation, and the BI rate affects simultaneously on non performing loan of conventional bank and non performing financing of sharia bank in short term and long term. LDR or FDR has negative effect of non performing loan and non performing financing in long term, but has no effect in short term. CAR has positive effect on non performing loan of conventional bank in short term and long term, while for sharia bank CAR has no effect in short term but has negative effect in long term. GDP has positive effect on non performing loan of conventional bank in short term and long term, while in non performing financing of sharia bank, GDP does not affect in short term but has positive effect in long term. Inflation does not affect on non performing loan of conventional bank in short term and long term, while for sharia bank inflation has negative effect to non performing financing in short term but has no effect in long term. BI rate has no effect on non performing loan of conventional bank and non performing financing of sharia bank in short term, but has positive effect on non performing loan of conventional bank and negativel effect on non performing financing of sharia bank in long term. Keywords: NPL, NPF, LDR, CAR, macroeconomic, ECM.